The Mediating Effect of Depressive Symptoms on the Relationship between Activity Engagement and Cognitive Function among Older Adults. - Kim, Da Eun; Kim, Bokyoung (Research in Community & Public Health Nursing (RCPHN), 2025)
Purpose: Engaging in activities in later life is beneficial for maintaining cognitive function. This study examined whether depressive symptoms mediate the relationship between activity engagement and cognitive function among older adults. Methods: A secondary data analysis was conducted using the 2022 Health and Retirement Study, including 2,741 participants aged 65 years and older. Mediation analyses were performed using SPSS PROCESS Macro Model 4 with bootstrapping. Results: A partial mediating effect of depressive symptoms was identified in the relationship between different types of activity engagement (e.g., physical, cognitive, and social activities) and cognitive function. The standardized indirect effects of depressive symptoms were β=.02 (95% boot CI=.01 to .03) for physical activity, β=.01 (95% boot CI=.01 to .02) for cognitive activity, and β=.02 (95% boot CI=.01 to .03) for social activity. Conclusion: These findings suggest that activity engagement may enhance cognitive function by reducing depressive symptoms among older adults. The results highlight the importance of developing and strengthening community-based physical, cognitive, and social activity programs that incorporate depressive symptom management as practical strategies to prevent cognitive decline in older adults.